Representasi Perempuan dalam Politik (Studi Pemilihan Legislatif Kota Dumai Periode 2019-2024) - Ramlan Darmansyah; Ade Sartika (Journal Civics and Social Studies, 2021)
The research was motivated by the existence of problems related to the interests of women which needed representation of women in the legislative body and also influences the provisions in Law Number 8 of 2012 concerning the General Election of Members of the DPR, DPD and DPRD relating to the 30% quota for women's representation. The formulation of the problem in this research is what is the form of legal guarantee for women's representation in the political sphere?. Then second, what is the level of vote acquisition of PPP women legislative candidates in the 2019-2024 election period in Dumai City ?. The purpose of this research is to see the certainty of legal guarantees for women's representation in the political realm and to see the level of vote acquisition of women legislative candidates for the PPP party in the 2019-2024 elections in Dumai City.  The focus of this research is to examine the results of women's vote acquisition in politics, especially in the Dumai City United Development Party (PPP) for the 2019-2024 period. This research is a research that uses the literature study method, where the data used comes from materials such as books, journals, and the results of research libraries from various references. The results of this study indicate that the results of women's votes from the United Development Party (PPP) in Dumai City have decreased significantly. This is because none of the women legislative candidates have succeeded in holding the legislative seats as representatives of women in the political arena.Keywords: Representation, Women, Politics, Political Parties, Votes